Interstitial Fluid in Lipedema and Control Skin - Marisol Allen; Michael Schwartz; Karen L. Herbst (Mary Ann Liebert, 2020)
Background: Fluid in lymphedema tissue appears histologically as spaces around vessels and between dermal skin fibers. Lipedema is a painful disease of excess loose connective tissue (fat) in limbs, almost exclusively of women, that worsens by stage, increasing lymphedema risk. Many women with lipedema have hypermobile joints suggesting a connective tissue disorder that may affect vessel structure and compliance of tissue resulting in excess fluid entering the interstitial space. It is unclear if excess fluid is present in lipedema tissue. The purpose of this study is to determine if fluid accumulates around vessels and between skin fibers in the thigh tissue of women with lipedema. Methods: Skin biopsies from the thigh and abdomen from 30 controls and 80 women with lipedema were evaluated for dermal spaces and abnormal vessel phenotype (AVP): (1) rounded endothelial cells; (2) perivascular spaces; and (3) perivascular immune cell infiltrate. Women matched for body mass index (BMI) and age were considered controls if they did not have lipedema on clinical examination. Data were analyzed by analysis of variance (ANOVA) or unpaired t-tests using GraphPad Prism Software 7. p?<?0.05 was considered significant. Results: Lipedema tissue mass increases beginning with Stage 1 up to Stage 3, with lipedema fat accumulating more on the limbs than the abdomen. AVP was higher in lipedema thigh (p?=?0.003) but not abdomen skin compared with controls. AVP was higher in thigh skin of women with Stage 1 (p?=?0.001) and Stage 2 (p?=?0.03) but not Stage 3 lipedema versus controls. AVP also was greater in the thigh skin of women with lipedema without obesity versus lipedema with obesity (p?<?0.0001). Dermal space was increased in lipedema thigh (p?=?0.0003) but not abdomen versus controls. Dermal spaces were also increased in women with lipedema Stage 3 (p?<?0.0001) and Stage 2 (p?=?0.0007) compared with controls. Conclusion: Excess interstitial fluid in lipedema tissue may originate from dysfunctional blood vessels (microangiopathy). Increased compliance of connective tissue in higher stages of lipedema may allow fluid to disperse into the interstitial space, including between skin dermal fibers. Lipedema may be an early form of lymphedema. ClinicalTrials.gov: NCT02838277.